Ultrastrong and ductile steel welds achieved by fine interlocking microstructures with film-like retained austenite - Moon, Joonoh; Bae, Gyuyeol; Jeong, Bo-Young; Shin, Chansun; Kwon, Min-Ji; Kim, Dong Ik; Choi, Dong-Jun; Lee, Bong Ho; Lee, Chang-Hoon; Hong, Hyun-Uk; Suh, Dong-Woo; Ponge, Dirk (Nature Publishing Group, 2024)
The degradation of mechanical properties caused by grain coarsening or the formation of brittle phases during welding reduces the longevity of products. Here, we report advances in the weld quality of ultra-high strength steels by utilizing Nb and Cr instead of Ni. Sole addition of Cr, as an alternative to Ni, has limitations in developing fine weld microstructure, while it is revealed that the coupling effects of Nb and Cr additions make a finer interlocking weld microstructures with a higher fraction of retained austenite due to the decrease in austenite to acicular ferrite and bainite transformation temperature and carbon activity. As a result, an alloying design with Nb and Cr creates ultrastrong and ductile steel welds with enhanced tensile properties, impact toughness, and fatigue strength, at 45% lower material costs and lower environmental impact by removing Ni.